Synthetic Cells: Toward Functional Synthetic Cells: In‐Depth Study of Nanoparticle and Enzyme Diffusion through a Cross‐Linked Polymersome Membrane (Adv. Sci. 7/2019). Issue 7 (3rd April 2019) - Gumz, Hannes; Boye, Susanne; Iyisan, Banu; Krönert, Vera; Formanek, Petr; Voit, Brigitte; Lederer, Albena; Appelhans, Dietmar
Abstract : Synthetic cells demand simultaneous and sequential tasks for developing next generation therapeutics. In article number 1801299, Albena Lederer, Dietmar Appelhans, and co‐workers report the integration of cell‐like functions in polymersomes. Through post‐loading of polymersomes, the control over protein location is discussed, essential for the exchange of biologically active materials in synthetic cells. Cover image designed by Dr. Josef Brandt.